Assessment of Dengue Severity via Correlation of Aspartate Aminotransferase/ Platelet Ratio Index with Other Biochemical Markers in Patients with Dengue Admitted To a Teaching Hospital in Lahore - Hafiza Farah Masood; Qurratul Ain; Hafiz Zoha Iqbal; Noor Shahid; Muhammad Raza Shafiq; Salman Farooq Dar (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To assess correlation of Aspartate Aminotransferase (AST) to platelet ratio index with other biochemical markers such as white cell count, platelet count, hemoglobin, hematocrit and liver function tests in patients of dengue fever for disease severity. Methods: Data was collected from 223 dengue fever patients admitted to a hospital setting in an out- break of 2022. Binary logistic regressions analysis was employed. AST to Platelet Ratio Index (APRI) was calculated and all parameters were studied to assess their association with the disease sever- ity. Severity of dengue was based on development of complications like bleeding, shock, end organ damage and duration of stay in the hospital. Results: The analysis done by software SPSS version 26.0 showed that 3.6% of the patients were se- verely ill while 96.4% were non severe with mean duration of stay in the hospital of 4.95 days. Univariate analysis showed ALT and age have positive correlation with disease severity with CI 95% and APRI significant positive correlation was at CI 90%. Multivariate analysis showed age and APRI to have association with disease severity with OR 1.06 and OR 1.16 respectively (p <0.05). Area under the Receiver Operating Characteristic (ROC) curve for APRI was 0.59. Conclusion: In addition to other biochemical parameters APRI can be used as an independent marker of predicting severity of disease in dengue patients thus it can add value in timely management of the dengue patients.